Meat in the Sandwich: The Impact of Changing Policy Contexts and Local Management of Schools on Principals’ Work in New Zealand 1989-2009 - Noeline Alcorn (New Zealand Journal of Teachers' Work)
The impact of principal leadership on school outcomes, particularly student achievement, is assuming unprecedented attention internationally. Official discourses often assume that principals can be trained to achieve prescribed outcomes through the employment of learned strategies. Such claims are challenged by critical leadership scholars who insist on the significance of context. This paper explores the impact of policy contexts on the work of a small group of experienced principals in New Zealand over a period of 20 years. During that time, they often struggled to reconcile their own espoused educational principles with policy imperatives in a small country where Local Management of Schools (LMS) has been extreme. It argues that national policy discourse around competition, curriculum and achievement, together with formal accountability to local lay Boards of Trustees (BOTs), are sources of tension and moral ambiguity, which tempt principals to comply and play the game for the sake of their schools. Principals are also caught between local and national accountabilities. In spite of this, principals in the study maintained an educational vision encompassing the wider social context of New Zealand education and retained a sense of personal agency.